Forecasting consumers' switching to disruptive technological innovations : a bounded rationality and self-evaluation perspective - Kacha Chotchaisatit; Badir, Yuosre F. M.; Junaid, Muhammad; Pal, Indrajit; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
Consumers' switching to disruptive technological innovations is critical to firms' long term success. While existing theories and frameworks broadly explain innovation adoption, understanding the switching process specific to disruptive innovations remains underexplored. The literature indicates that the switching to disruptive technologies involves decision-making processes that differ significantly from those associated with continuous innovations.This study examines consumers{u2019} switching behavior through the lens of bounded rationality and self-evaluation. It integrates: (1) prospect theory, which posits that consumers assess relative gains and losses when considering product replacement; (2) two-system thinking, highlighting the interplay of rational (economic) and non-rational (emotional) decision processes; and (3) self-evaluation constructs i.e., self-image and self-efficacy, reflecting consumers{u2019} self-assessments in relation to the innovation. These perspectives are synthesized into a moderated mediation model, conceptualized as a comparative mind. A key contribution is the introduction of a second-order construct, Comparative Innovation Premium (CIP), representing the superior hedonic and economic value consumers perceive in a disruptive innovation.The smartwatch, as an Internet-of-Things (IoT) device, serves as the focal disruptive innovation in this study. Field survey data from 1,114 Thai consumers were analyzed using structural equation modeling (SEM) to test the proposed hypotheses. The results reveal that Comparative Innovation Premium (CIP) significantly and positively influences consumers{u2019} switching intentions. Additionally, self-evaluations play a substantial role in shaping consumers{u2019} switching intentions.The findings advance theoretical understanding by deepening our understanding of the psychological mechanisms and Comparative Innovation Premium (CIP) underlying consumer switching to disruptive innovations. This research equips both scholars and managers with a strategic framework to anticipate and influence consumer behavior in an era of rapid technological disruption.
A dissertation submitted in partial fulfillment of the requirements for the degree of Doctor of Business Administration
Thesis (Ph.D.) - Asian Institute of Technology, 2025
Keywords: Disruptive technologies; Technological innovations -- Management; Consumers